Percutaneous coronary intervention following Fontan procedure. (June 2020) - Subahi, Ahmed; Forbes, Thomas; Ali, Omar E.
Abstract: Fontan procedure is known to increase the risk of thromboembolic events. However, coronary artery thrombotic occlusion is rarely reported in patients with Fontan procedure. We present a case of a 10-year-old boy with hypoplastic left heart syndrome palliated with a Fontan procedure who presented with myocardial infarction secondary to thrombotic occlusion of the left circumflex coronary artery. He underwent successful percutaneous coronary intervention with thrombus aspiration, balloon angioplasty, and stent placement, highlighting the necessity of collaboration between congenital and adult cardiologists to treat acute coronary syndrome among this challenging young population.